Takaphone takaful / Muhammad Waizzulhakim Othamannor ... [et al.] - Othamannor, Muhammad Waizzulhakim; Mohd Jamil, Mohd Mazwan; Mohammad Hatta, Mohammad Firdaus; Syed Alwi, Sharifah Faigah (2021)
The Malaysian Takaful industry has continued its upward trend in promoting and enabling more Malaysians to obtain new Takaful protection. Takaful is an alternative to conventional insurance because conventional insurance includes interest, uncertainty and gambling, all of which are prohibited in Islamic law. In order to enhance its position in the sector and grow its market share over the conventional insurance industry, Takaful has adopted a variety of product available to the general public. As the technology is rapidly changing, phone manufacturer companies become innovative to ensure competitiveness in the markets. Despite of increase of the new innovations, the survivability of smartphones such as armored phone casings and tempered glass, there isn't much that can be done in order to improve the human aspect. Therefore, Takaful plan focuses only on smartphones. Hence, this study aims to gain knowledge and awareness as well as propose new Takaful product related to protection of smartphones. This study has applied both qualitative and quantitative methods in which 40 questionnaires have been distributed to respondents via online survey to anyone who owns smartphones and prioritizes the Klang Valley area. As a result, the innovation of TakaPhone in order to protect smartphones is the best solution instead of warranty given by the vendor and manufacturer for smartphone users.